Near-isotropic enhancement of the 20 K critical current of REBa2Cu3O7 coated conductors from columnar defects. (9th March 2023) - Strickland, Nicholas M; Wimbush, Stuart C; Soman, Arya Ambadiyil; Long, Nicholas J; Rupich, Martin W; Knibbe, Ruth; Li, Ming; Notthoff, Christian; Kluth, Patrick
Abstract: Normal-incidence irradiation by 100 MeV Ag ions is used to improve flux pinning in previously optimised commercial REBCO tapes from the American Superconductor Corporation. We observe distinct critical-current anisotropy enhancements below and above 40 K. Above 40 K a strong c -axis peak appears in the angular dependence of the critical current, as is usually expected upon the introduction of columnar defects. The critical current is enhanced significantly but only for a limited range of field angles. Close to the parallel-field direction there is no enhancement or even a reduction in critical current. Below 40 K, on the other hand, the enhancement is much broader with respect to field angle, creating an almost isotropic response at 20 K, 3 T. The absence of a prominent c -axis peak does not indicate a lack of pinning, since the absolute value of the critical current still increases by a factor of 2.8 compared to an unirradiated sample. Instead, we postulate that pre-existing point-like pinning centres act to mediate an interaction between the existing planar and newly-introduced columnar pins, broadening both contributions. The point-like pins become less effective with increasing temperature as the coherence length increases, leading to a reduction in this interaction and a separation of the individual peaks relating to planar and columnar pins. At 20 K, we achieve an enhancement in the angular-minimum critical current by a factor of 2.7, in a material that had already been process-optimised for low-temperature pinning.